Membongkar Imperialisme dalam Kebijakan Pajak Usaha Mikro Kecil dan Menengah (UMKM) - Yuyung Rizka Aneswari (Universitas Trunojoyo Madura, 2018)
This article aims to criticize the fairness of the application of the final tariff incometax for MSME This research is in a critical paradigm using Sukarno's thinkingMarhaenism as a tool to criticize. Marhaenisme has three basic values, namely SosioNasionalisme, Sosio Demokrasi dan Ketuhanan yang Maha Esa. The results showthat taxation policy does not take into account the unique characteristics of SMEs,allegedly only concerned with a certain type of dolongan and loaded with the spiritof materialism. This research has a policy contraibution that provides a discourse forthe government on a fair tax implementation scheme, especially for MSMEs.